Pengaruh Teamwork dan Self-Efficacy Terhadap Produktivitas Karyawan Pada PT United Farmatic Indonesia: The Influence of Teamwork and Self-Efficacy on Employee Productivity at PT United Farmatic Indonesia - Zihan Natasya; Usran Masahere (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Employee productivity is an important factor in supporting the achievement of organizational goals. Optimal productivity levels can be influenced by various factors, including teamwork and self-efficacy. Effective teamwork enables good communication and coordination among employees, while self-efficacy refers to an individual’s belief in their ability to accomplish work tasks. This study aims to examine the effect of teamwork and self-efficacy on employee productivity at PT. UFI. The research employed a quantitative method by distributing questionnaires through Google Forms. The population of this study consisted of 105 office employees at PT. UFI, with 77 respondents selected using a purposive sampling technique. Hypothesis testing was conducted using t-tests and an F-test. The results indicate that teamwork has a positive and significant effect on productivity (t-value = 4.128 > 1.992; sig. = 0.003), and self-efficacy also has a positive and significant effect on productivity (t-value = 4.913 > 1.992; sig. = 0.000). Simultaneously, teamwork and self-efficacy significantly affect productivity, as indicated by an F-value of 137.842 > 3.11 with a significance value of 0.000. In conclusion, teamwork and self-efficacy contribute 78.3% to employee productivity, while the remaining 21.7% is influenced by other variables not examined in this study.